A potential energy field (PEF) approach to the design of a compliant self-guiding statically-balanced straight-line mechanism. (August 2017) - Radaelli, G.; Herder, J.L.
Highlights: An approach to the design of compliant mechanisms based on PEFs is presented. PEFs characterise the elastic behaviour of systems over a large motion space. Parallel subsystems are easily connected to characterise the assembled system. Example: a straight-line mechanisms, statically balanced along the line of motion. Abstract: For the conception of compliant mechanisms various design aids have been proposed, including some graphical ones. In this work we propose to use the potential energy field of elastic systems to characterise their behaviour over a large motion area. The system and its characterisation can be interactively adapted to obtain a behaviour of interest. The behaviour is fine-tuned by a shape optimization procedure. This approach is elaborated in this paper for systems comprising curved planar beams. A design example is presented that can realise an unconstrained straight-line motion with a constant potential energy level, comprising four symmetrically arranged beams.